Researching Child Authors: Which Questions (not to) Ask - Elisabeth Wesseling (Humanities, 2019)
It used to be taken for a given fact that children’s literature is written by adults for children. This assumption is contested by the emergence of “another children’s literature”, namely literature about, for, and by children. Facilitated by digital platforms, this alternative type of children’s literature is gathering momentum, compelling us to rethink the (im)possibilities of children’s creative agency. As research into children’s literature is largely premised upon the asymmetry between adult authorship and juvenile readership, we need to rethink some fundamental tenets of this academic field in order to come to terms with child authorship. This article reviews leading publications on the topic, to address the question of how we can best acknowledge, facilitate, and appreciate children’s creative agency as an indispensable dimension of their emergent citizenship. Methodological deliberations are illustrated with references to primary works by child authors about topical societal issues such as ethnic conflict, homelessness, and migration. Its aim is not so much to provide a complete survey of all available publications on the topic, but rather to stake out representative publications that exemplify more and less fruitful approaches to the problem at hand.